2009
DOI: 10.2138/am.2009.3144
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Raman spectrum of a high-pressure Li-rich majoritic garnet, (Li2Mg)Si2(SiO4)3

Abstract: A Li-rich majoritic garnet (LiMGt), (Li 2 Mg)Si 2 (SiO 4 ) 3 , was synthesized at 15 GPa and 1500 °C and its structure studied with single-crystal X-ray diffraction and Raman spectroscopy. It is cubic with space group Ia3d and unit-cell parameters a = 11.2660(2) Å and V = 1429.91(1) Å 3 . The 8-, 6-, and 4-coordinated cation sites in LiMGt are occupied by (Li + + Mg 2+ ), Si 4+ , and Si 4+ , respectively. Whereas the SiO 6 octahedron is nearly regular, the XO 8 dodecahedron is the most distorted of all known s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Based on equilibrium fractionation models at a range of temperatures relevant to weathering and igneous processes (273-2,000 K), the δ 26 Mg and δ 7 Li values of garnet (CN = 8) are predicted to be lower (Schauble, 2011;Huang et al, 2013) compared to hornblende (CN = 6/5, Wunder et al, 2007) and for Mg isotopes this is what we observe (Figure 3). In contrast, the δ 7 Li value of garnet is not markedly lower than the other minerals as would be predicted if Li was in the dodecahedral site (e.g., Yang et al, 2009). Studies of lithium-rich synthetic garnets have demonstrated that Li can be contained in sites with CNs of 4 and 6 (Mazza, 1988;O'Callaghan et al, 2008;Cussen, 2010;Rettenwander et al, 2016).…”
Section: Inter-mineral Isotope Variationmentioning
confidence: 87%
“…Based on equilibrium fractionation models at a range of temperatures relevant to weathering and igneous processes (273-2,000 K), the δ 26 Mg and δ 7 Li values of garnet (CN = 8) are predicted to be lower (Schauble, 2011;Huang et al, 2013) compared to hornblende (CN = 6/5, Wunder et al, 2007) and for Mg isotopes this is what we observe (Figure 3). In contrast, the δ 7 Li value of garnet is not markedly lower than the other minerals as would be predicted if Li was in the dodecahedral site (e.g., Yang et al, 2009). Studies of lithium-rich synthetic garnets have demonstrated that Li can be contained in sites with CNs of 4 and 6 (Mazza, 1988;O'Callaghan et al, 2008;Cussen, 2010;Rettenwander et al, 2016).…”
Section: Inter-mineral Isotope Variationmentioning
confidence: 87%
“…An exception are the 259-1113 ppm Li in almandine from leucocratic granulite at Horní Bory, Czech Republic, corresponding to 0.019-0.079 Li pfu, determined by laser ablation-inductively coupled plasma-mass spectroscopy (Cempírek et al 2010 and unpublished data). According to Cempírek et al (2010) (Yang et al 2009) or sites occupied by Li in synthetic garnets. The majority of synthetic Li garnets are compounds of Li with REE, Ta, Nb, Te, Zr, and Ba that are valued for their high-ionic conductivity (e.g., Cussen 2006Cussen , 2010O'Callaghan and Cussen 2007;Wang and Lai 2012).…”
Section: Assumed Cation Occupanciesmentioning
confidence: 99%
“…In the latter instance, the substitution of sodium into the structure is intimately tied to both Ti and/or Si substitution into the octahedral site: therefore, this component incorporates a coupling between the classic majorite substitution and sodium/alkali substitution into garnets. Indeed, while the majorite substitution is typically formulated as M 3 Al 2À2x M x Si x (Si 3 O 12 ) where M represents divalent cations and x is the mole fraction of majorite, garnets that have the formula A 2 1+ MSi 2 (Si 3 O 12 ) have been observed, where A is an alkali element (e.g., Pacalo et al, 1992;Bobrov et al, 2008;Yang et al, 2009). The resultant garnet can be termed hypersilicic and, as described below, we find the incorporation of a sodium/alkali component to be more compatible with the compositional patterns that we observe within suites of natural majoritic garnets.…”
Section: Rationale For Calculation Of Majoritic Garnet Substitutionsmentioning
confidence: 99%